Prevalence and risk factors of early postoperative seizures in patients with glioma: a systematic review and meta-analysis - Sun, Bo; Sun, Yuchen; Wang, Zijian; Zhao, Chao; Yang, Liang (Frontiers in Neurology, 2024)
Objective This study aimed to explore the prevalence and risk factors of early postoperative seizures in patients with glioma through meta-analysis. Methods Case–control studies and cohort studies on the prevalence and risk factors of early postoperative seizures in glioma patients were retrieved from various databases including CNKI, Wanfang, VIP, PubMed, Embase, Cochrane Library, and Web of Science, and the retrieval deadline for the data was 1 April 2023. Stata15.0 was used to analyze the data. Results This review included 11 studies consisting of 488 patients with early postoperative seizures and 2,051 patients without early postoperative seizures. The research findings suggest that the prevalence of glioma is complicated by seizures (ES = 19%, 95% confidence interval [CI] [14%−25%]). The results also indicated a history of seizures (RR = 1.94, 95% CI [1.76, 2.14], P = 0.001), preoperative dyskinesia (RR = 3.13, 95% CI [1.20, 8.15], P = 0.02), frontal lobe tumor (RR = 1.45, 95% CI [1.16, 1.83], P = 0.001), pathological grade ≤2 (RR = 1.74, 95% CI [1.13, 2.67], P = 0.012), tumor≥ 3 cm (RR = 1.70, 95% CI [1.18, 2.45], P = 0.005), tumor resection (RR = 1.60, 95% CI [1.36, 1.88], P = 0.001), tumor edema ≥ 2 cm (RR = 1.77, 95% CI [1.40, 2.25], P = 0.001), and glioma cavity hemorrhage (RR=3.15, 95% CI [1.85, 5.37], P = 0.001). The multivariate analysis results showed that a history of seizures, dyskinesia, tumor ≥3 cm, peritumoral edema ≥2 cm, and glioma cavity hemorrhage were indicated as risk factors for glioma complicated with early postoperative seizures. Significance Based on the existing evidence, seizure history, dyskinesia, frontal lobe tumor, pathological grade ≤2, tumor ≥3 cm, partial tumor resection, edema around tumor ≥2 cm, and glioma cavity hemorrhage are indicated as risk factors for glioma complicated with early postoperative seizures.